ER stress promoted MAMs formation and ER-Mito Ca2+ transfer: implication for fluoride-induced hippocampal neuronal injury and cognitive deficits in mice - Siman Lin; LuYang Cao; Yuzhe Zhou; Shengdan Liu; Yue Yan; Qiwei Zhang; Quan Yuan; Yufei Gao; Ge Du; Jun Hu; Dongmei Wang; Hua Fan (Chemico-Biological Interactions, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Co-pyrolysis of polyphenylene sulfide with various plastics: Sulfur migration and interaction mechanism - Yue Sheng; Longfei Tang; Weitong Pang; Siman Nie; Lu Ding; Xueli Chen; Xudong Song; Fuchen Wang (Journal of Environmental Chemical Engineering, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Effect of polymer compositions on the combustion of RDX explosive - Siman Guan; Zhijun Wang; Jianping Yin; Ruijie Hao; Qing Ji (Chemical Engineering Journal, 2026)

Rapid geographical origin identification and functional compound content prediction of Chrysanthemum (“Gongju”) using excitation–emission matrix fluorescence spectroscopy coupled with chemometrics - Xue Guo; Youyou Wang; Ruibin Bai; Yao Chen; Siman Wang; Hui Wang; Yutong Hua; Tong Wang; Jian Yang (Food Chemistry, 2025)

Functional genes abundance associated with cellulose and hemicellulose degradation reveals the difference of wheat straw decomposition with contrasting tillage histories - Pengfei SHEN; Siman GAO; Xiong WANG; Fei CHEN; Xiaoxia WEN; Weiyan WANG; Yuncheng LIAO (Pedosphere, 2025)

Fast response and stable dyed cellulose nanofibrous films for shrimp spoilage detection - Fuyuan Ding; Siman Long; Xiaowei Huang; Xin Wang; Roujia Zhang; Jiyong Shi; Yang Zou; Xiaobo Zou (Food Chemistry, 2025)

Preparation of Fangxian traditional Xiaoqu and its evolution of microbial communities and aroma compounds during fermentation - Siman Zheng; Mingquan Huang; Wu Yang; Zhongchao Wang; Qing Ren; Hailan Li; Jihong Wu; Nan Meng; Jinchen Li; Bowen Wang (Food Research International, 2025)

Fast prediction of diverse rare ginsenoside contents in Panax ginseng through hyperspectral imaging assisted with the temporal convolutional network-attention mechanism (TCNA) deep learning - Youyou Wang; Siman Wang; Yuwei Yuan; Xiaoyong Li; Ruibin Bai; Xiufu Wan; Tiegui Nan; Jian Yang; Luqi Huang (Food Control, 2024)

Geographical verification of Pleuropterus multiflorus thunb. by functional compounds, stable isotope ratios, and multielement combined with machine learning methods - Feng Xiong; Siman Wang; Chuanzhi Kang; Youyou Wang; Ruibin Bai; Haiyan Li; Jian Yang; Lanping Guo (Food Chemistry, 2024)

Prediction performance and reliability evaluation of three ginsenosides in Panax ginseng using hyperspectral imaging combined with a novel ensemble chemometric model - Youyou Wang; Siman Wang; Ruibin Bai; Xiaoyong Li; Yuwei Yuan; Tiegui Nan; Chuanzhi Kang; Jian Yang; Luqi Huang (Food Chemistry, 2024)

Self-assembly of mixed valence polyoxovanadate-based metal-organic frameworks for enhanced CO2 photoreduction - Jilei Wang; Hu Xu; Qin Wang; Jiulin Zhou; Xinying Xiang; Siman Li; Hua Mei; Yan Xu (Chemical Engineering Journal, 2023)

Conversion of swine manure into biochar for soil amendment: Efficacy and underlying mechanism of dissipating antibiotic resistance genes - Yan He; Xin Zhao; Siman Zhu; Long Yuan; Xinyi Li; Zhihan Feng; Xuan Yang; Ling Luo; Yinlong Xiao; Yan Liu; Lilin Wang; Ouping Deng (Science of The Total Environment, 2023)

Application of hyperspectral imaging assisted with integrated deep learning approaches in identifying geographical origins and predicting nutrient contents of Coix seeds - Youyou Wang; Feng Xiong; Yue Zhang; Siman Wang; Yuwei Yuan; Cuncun Lu; Jing Nie; Tiegui Nan; Bin Yang; Luqi Huang; Jian Yang (Food Chemistry, 2023)

Designing and the Pilot Trial of Bivalve Molluscan Fishing Quotas on Maoming Coastal Waters of China, Northern South China Sea - Shaoliang Lyu; Siman Deng; Kun Lin; Jiawei Zeng; Xuefeng Wang (Frontiers in Marine Science, 2022)
In the context of the declining fishery resources, some active management measures have been taken to strive for the sustainable development of fisheries. However, these input-oriented control management measures have not realized the expectation in alleviating the depressing depletion of fishery resources. The fishing quota (FQ) system, an output-oriented control management method, has been proved to be effective in curbing overfishing and conserving fishery resources. However, it has not been formally implemented in China until now. Thus, it is urgent to start the pilot trial on the implementation of the FQ system in China. We firstly formulated a framework for the FQ system on bivalve fisheries and then conducted an empirical analysis based on the field survey of bivalve mollusks in Maoming shallow waters, Guangdong, northern South China Sea. The species composition, dominant species, and density distribution of bivalves were analyzed. The swept-area method was used to assess the total allowable catch (TAC) of bivalves. Each step of the FQ system was discussed in depth. Results showed that a total of 45 bivalve species were identified. Meretrix planisulcata and Ruditapes philippinarum were the two dominant species. The spatial distribution of density varied largely. The estimated TAC value is 4.28 × 10 5 kg which can be allocated to fishermen under the regulations of the FQ system. Finally, the framework for the FQ system was improved in every step of the future procedure, including target species selection, TAC determination, quota allocation, catch report, and fishing supervision. The general framework of the FQ system in this study can also be referenced to other economically important fish or other marine organisms.

Bacterivore nematodes stimulate soil gross N transformation rates depending on their species - Tongbin Zhu; Cheng Yang; Jun Wang; Siman Zeng; Manqiang Liu; Jinling Yang; Bing Bai; Jianhua Cao; Xiaoyun Chen; Christoph Müller (Biology and Fertility of Soils, 2018)